Microbial prevalence of Kaptai lake from two different spots - Neha, Amreen Nahin; Alam, Sharmila; Saha, Pretom Kumar (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2023.